2019
DOI: 10.1101/528729
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Verticillium dahliae strains that infect the same host plant display highly divergent effector catalogs

Abstract: 20 42 strains that are able to infect the same host plant harbor highly divergent 43 LS effector repertoires. Furthermore, we observed differential V. dahliae 44 core effector gene expression between host plants. Our data suggest that 45 different V. dahliae lineages utilise divergent effector catalogs to colonize 46 the same host plant, suggesting considerable redundancy among the 47

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 57 publications
2
23
2
Order By: Relevance
“…Resampling was completed using the bootstrap method with 1000 replicates. Pathogenicity on tomato confirmed in this study or in other studies using universally susceptible standard "Bonny Best" (Faino et al, 2015;Gibriel et al, 2019).…”
Section: Phylogenetic Analysissupporting
confidence: 83%
See 2 more Smart Citations
“…Resampling was completed using the bootstrap method with 1000 replicates. Pathogenicity on tomato confirmed in this study or in other studies using universally susceptible standard "Bonny Best" (Faino et al, 2015;Gibriel et al, 2019).…”
Section: Phylogenetic Analysissupporting
confidence: 83%
“…A study of the VdLs17 genome in 2011 showed only 127 effectors, however, the method by which they were classified as effectors was by sequence length (<400 bp) and being rich in cysteine (Klosterman et al, 2011). A more recent study of the VdLs17 (using SignalP v4.1 and EffectorP v1.0) reported 179 (Gibriel et al, 2019). In this study, additional secreted effectors were found.…”
Section: Secreted Effector Genesmentioning
confidence: 57%
See 1 more Smart Citation
“…Examples comprise the wheat pathogens Zymoseptoria tritici[67] and Blumeria graminis f. sp. tritici[68], and the broad host range pathogen Verticillium dahlia[69]. Moreover, different strains can encode different alleles of the same effector gene; this was, for example, reported for the low complexity regions containing Ustilago maydis effector Rsp3[58].Several reports suggest that effector proteins containing low complexity regions can play important roles in virulence[37,70], and results presented in the present work suggest that different fungal lifestyles contribute to the evolution of low complexity regions in effector proteins.ConclusionsA comparative genomics study with 121 plant colonizing fungi representing six different lifestyles showed that protein type (cytoplasmic or secreted), protein age (ancestral proteins conserved in most species or recent species-specific proteins), and lifestyle of different fungal species contribute to the evolution of low complexity regions in effector proteins.…”
supporting
confidence: 76%
“…However, based on previously performed RNA sequencing experiments, no expression of any of these candidates could be monitored during colonization of Arabidopsis thaliana, Nicotiana benthamiana or cotton plants (Extended data Fig. 6) 17,20,27,28 . Additionally, in vitro cultivation of V. dahliae in the presence of E. coli , B. subtilis or T. viride , or of peptidoglycan to mimic bacterial encounter, did not lead to induction of any of the effector candidate genes (Extended data Fig.…”
Section: Introductionmentioning
confidence: 99%